A history of modern Iran - Abrahamian, Ervand, 1940- (Cambridge, UK ; New York : Cambridge University Press, 2008)
From the Publisher: In a reappraisal of Iran's modern history, Ervand Abrahamian traces its traumatic journey across the twentieth century, through the discovery of oil, imperial interventions, the rule of the Pahlavi's and, in 1979, revolution and the birth of the Islamic Republic. In the intervening years, the country has experienced a bitter war with Iraq, the transformation of society under the clergy and, more recently, the expansion of the state and the struggle for power between the old elites, the intelligentsia and the commercial middle class. The author is a compassionate expositor. While he adroitly negotiates the twists and turns of the country's regional and international politics, at the heart of his book are the people of Iran. It is to them and their resilience that this book is dedicated, as Iran emerges at the beginning of the twenty-first century as one of the most powerful states in the Middle East
List of maps -- List of illustrations -- List of tables and figures -- Chronology -- Glossary -- A political who's who of modern Iran -- Preface -- Introduction -- 1. 'Royal despots' : state and society under the Qajars -- 2. Reform, revolution, and the Great War -- 3. The iron fist of Reza Shah -- 4. The nationalist interregnum -- 5. Muhammad Reza Shah's White Revolution -- 6. The Islamic Republic -- Notes -- Bibliography -- Further reading -- Index
Includes bibliographical references (pages 196-223) and index
Keywords: Iran -- History -- 20th century